Reexploring the Anatomy of the Distal Humerus for its Role in Providing Vascularized Bone. Issue 1 (January 2018) - Carr, Logan W.; Brooke, Sebastian M.; Johnson, T. Shane; Michelotti, Brett F.
Abstract : Background: The lateral arm flap is used for composite defects in need of vascularized soft tissue, skin, and bone. From its original description, the distal humeral metaphysis can be included with the flap, supplied by the periosteal extensions of the posterior branch of the radial collateral artery. We sought to reexplore the anatomy of the lateral arm to determine its utility as a donor site for vascularized bone. Methods: Twelve fresh, silicone-injected cadaver dissections were performed. Arteriovenous anatomy, pedicle length and diameter, and anatomic variability as well as photo documentation was recorded. Results: The distal extent of the deltoid, lateral intermuscular septum and lateral humeral epicondyle were identified before the dissection. A septocutaneous perforator was consistently located 10 cm proximal to the lateral humeral epicondyle, which could be used for a skin paddle to monitor. Harvest of a 1.5 cm × 2 cm corticocancellous bone graft was performed. Average pedicle length was 9.1 ± 1.1 cm, and average pedicle diameter was 1.74 ± 0.52 mm. The inferior lateral cutaneous nerve of the arm and the posterior cutaneous nerve of the forearm were consistently identified and preserved. Conclusion: The predictable anatomy of the lateral distal humerus make it an ideal donor site for small segments of vascularized bone.